BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Middle childhood weight stigmatization and appetite self-regulation as predictors of adolescent weight – A prospective mediation analysis - Nele Westermann; Annette M. Klein; Petra Warschburger (Appetite, 2025)

The role of microfibrillar-associated protein 4 (MFAP4) in the formation and function of splenic compartments during embryonic and adult life - Novica M. Milićević; Friederike Schmidt; Natalia Kunz; Kathrin Kalies; Živana Milićević; Anders Schlosser; Uffe Holmskov; Grith Lykke Sorensen; Jürgen Westermann (Cell and Tissue Research, 2016)

Polymorphisms in ACVRL1 and Endoglin Genes are Not Associated with Sporadic and HHT-Related Brain AVMs in Dutch Patients - Kim Boshuisen; Manon Brundel; Carolien G. F. de Kovel; Tom G. Letteboer; Gabriel J. E. Rinkel; Cornelis J. J. Westermann; Helen Kim; Ludmila Pawlikowska; Bobby P. C. Koeleman; Catharina J. M. Klijn (Translational Stroke Research, 2013)

Esperanto for histones: CENP-A, not CenH3, is the centromeric histone H3 variant - W. C. Earnshaw; R. C. Allshire; B. E. Black; K. Bloom; B. R. Brinkley; W. Brown; I. M. Cheeseman; K. H. A. Choo; G. P. Copenhaver; J. G. DeLuca; A. Desai; S. Diekmann; et al. (Chromosome Research, 2013)

Ultrastructural freeze-fracture immunolabeling identifies plasma membrane-localized syndapin II as a crucial factor in shaping caveolae - Dennis Koch; Martin Westermann; Michael M. Kessels; Britta Qualmann (Histochemistry and Cell Biology, 2012)

Role of CCL19/21 and its possible signaling through CXCR3 in development of metallophilic macrophages in the mouse thymus - Novica M. Milićević; Miloš D. Miljković; Živana Milićević; Milica Labudović-Borović; Xiaoping Wang; Martti Laan; Pärt Peterson; Troy D. Randall; Jürgen Westermann (Histochemistry and Cell Biology, 2011)

Metallophilic macrophages are fully developed in the thymus of autoimmune regulator (Aire)-deficient mice - Novica M. Milićević; Živana Milićević; Miloš D. Miljković; Milica Labudović-Borović; Martti Laan; Pärt Peterson; Kai Kisand; Hamish S. Scott; Ning Qu; Jürgen Westermann (Histochemistry and Cell Biology, 2009)

Metallophilic macrophages are lacking in the thymus of lymphotoxin-β receptor-deficient mice - Novica M. Milićević; Klaus Nohroudi; Milica Labudović-Borović; Živana Milićević; Klaus Pfeffer; Jürgen Westermann (Histochemistry and Cell Biology, 2006)

Localisation of fucoxanthin chlorophyll a/c-binding polypeptides of the centric diatom Cyclotella cryptica by immuno-electron microscopy - M. Westermann; E. Rhiel (Protoplasma, 2005)

Hereditary hemorrhagic telangiectasia: ENG and ALK-1 mutations in Dutch patients - T. G. W. Letteboer; R. A. Zewald; E. J. Kamping; G. de Haas; J. J. Mager; R. J. Snijder; D. Lindhout; F. A. M. Hennekam; C. J. J. Westermann; J. K. Ploos van Amstel (Human Genetics, 2005)

Effect of repeated treatment with high doses of selegiline on behaviour, striatal dopaminergic transmission and tyrosine hydroxylase mRNA levels - Themann C.; D. Alvarez Fischer; Groß S.; Westermann R.; Weihe E.; Kuschinsky K.; Schäfer M.; Ferger B. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2002)

Ultrastructure of Acaryochloris marina , an oxyphotobacterium containing mainly chlorophyll d - J. Marquardt; E. Mörschel; E. Rhiel; M. Westermann (Archives of Microbiology, 2000)

Membrane structure of caveolae and isolated caveolin-rich vesicles - M. Westermann; Heiko Leutbecher; Helmut W. Meyer (Histochemistry and Cell Biology, 1999)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Nutrient concentration relationships between the fourth petiole and upper-stem of potato plants - D. T. Westermann; S. M. Bosma; M. A. Kay (American Journal of Potato Research, 1994)

Zone-subsoiling effects on potato yield and grade - R. E. Sojka; D. T. Westermann; D. C. Kincaid; I. R. McCann; J. L. Halderson; M. Thornton (American Journal of Potato Research, 1993)

Specific gravity of Russet Burbank potatoes - G. E. Kleinkopf; D. T. Westermann; M. J. Wille; G. D. Kleinschmidt (American Journal of Potato Research, 1987)